Implementasi Hypnocounseling dalam Mengentaskan Masalah Siswa - Edriyansyah Edriyansyah; Suswati Hendirani; Selvia Netri; Yeni Ariyanti (Empowerment Counseling Journal, 2025)
This study aims to develop career module for deaf students using the Design-Based Research (DBR) approach. This study used a literature review method to analyse and synthesize previous research related to the development of career module for deaf students. The module is designed to address challenges such as communication barriers, limited vocational training, and social stigma faced by deaf students. Through a literature review method, the researcher explores various academic sources, including scholarly journals, books, and research articles, to build a theoretical framework and identify gaps in previous educational approaches. The module integrates career development theories, self-efficacy, and a multimodal approach to offer a more inclusive, authentic, and adaptive learning solution. The findings indicate that the success of this module is supported by the involvement of multiple stakeholders such as teachers, parents, and students, enriching the learning process. This module is also designed to promote the sustainability of inclusive education through the active engagement of various stakeholders. These findings contribute significantly to the improvement of inclusive education policies in Indonesia.